The Analysis of Predator Pricing at Shopee Based on Business Competition Law - Gaby Romauli Simarmata; Sabda Dian Nurani Siahaan; Lorena Hasibuan; Ayunda Fadilla; Firza Aditya; Gani Pinodana (PT FORMOSA CENDEKIA GLOBAL, 2023)
KPPU has prepared guidelines for selling at a loss or predatory pricing based on Law no. 5/1999, which has the potential to cause monopolistic practices and unfair business competition. This study uses qualitative research methods with descriptive data analysis, through documentation techniques and literature studies. In 2018, several online stores alleged predatory pricing, including Tokopedia, Bukalapak, Shopee and Lazada. Not all flash sales are included in this practice. Flash sale is a marketing strategy with big discounts for a limited time. The public is advised to be more careful in choosing and comparing prices and product quality from various stores. The same pictures and descriptions do not guarantee the same product. The industry must be aware of predatory pricing that endangers the business, but does not ignore competitors in the digital business space.